Komoditas Perkebunan di Provinsi Maluku Utara: Basis Ekonomi dan Tingkat Spesialisasi - Muhammad Zais M. Samiun; Musdar Muhammad; Muhammad Hasnin; Mina Nurul Rizky (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
North Maluku's economy continues to advance with the agricultural sector, particularly plantations, as the main contributor. Plantations have a positive impact on the economy with various value-added commodities. This study aims to analyse the economic base commodities and the level of specialisation of plantation subsector commodity development in North Maluku Province. The data used is secondary data with the main data of production volume of plantation subsector commodities at the national level, North Maluku Province, and district/city areas. The analysis method used was Location Quotient and Specialisation Index analysis method. The analysis results show that there are five commodities identified as economic base commodities in the plantation subsector, namely Nutmeg, Coconut, Clove, Cashew, and Cocoa. The five base commodities are evenly distributed in each district/city in North Maluku. The analysis shows that efforts to specialise commodity development have not been optimal in this province, including at the district/city level.